Edukasi Bahaya Penyalahgunaan Narkotika, Psikotropika, Dan Zat Adiktif Dan Pentingnya Kesehatan Reproduksi Bagi Remaja - Mahfudzah, Nur Arifah; Rahayu, Amelia Putri; Fitria, Fitria; Ridha, Ridha Amelia; Serang, Aditya Anugerah F; Stevani, Hendra; Dewi, Ratnasari (Jurnal Pengabdian Kefarmasian, 2024)
EducationOntheDangersofDrugAbuseandTheImportanceOfReproductiveHealthFor AdolescentsBackground, Adolescence is a transitional phase that is vulnerable to drug abuse and low awareness of reproductive health, which risks causing serious impacts. With the existence of health counseling which aims to improve students' understanding of the dangers of drug abuse and the importance of reproductive health for adolescents. Methods, interactive education sessions with presentations, and question and answer sessions to strengthen understanding. Results, this activity was attended by 29 students with 11 male students and 18 female students in class VIII UPT SMP Negeri 07 Makassar. There was an increase in student understanding from the results of the questionnaire which was originally for the "Good" category, namely 13.8%, increasing drastically to 86.2%. This is because interactive education is effective in improving students' understanding of the dangers of drug abuse and the importance of reproductive health for adolescents. Conclusion, with this counseling activity, students were able to improve their understanding of the dangers of drug abuse and the importance of reproductive health for adolescents.Latar Belakang, Masa remaja adalah fase transisi yang rentan terhadap penyalahgunaan narkoba dan rendahnya kesadaran kesehatan reproduksi, yang berisiko menimbulkan dampak serius. Dengan adanya penyuluhan kesehatan yang dimana bertujuan untuk meningkatkan pemahaman siswa-siswi tentang bahaya penyalahgunaan Napza dan pentingnya kesehatan reproduksi bagi remaja. Metode, sesi edukasi interaktif dengan presentasi, serta sesi tanya jawab untuk memperkuat pemahaman. Hasil, kegiatan ini diikuti oleh 29 siswa dengan 11 siswa laki-laki dan 18 siswa perempuan kelas VIII UPT SMP Negeri 07 Makassar. Terjadi peningkatan pemahaman siswa dari hasil kuisioner yang semula untuk kategori “Baik” yaitu 13,8% meningkat drastis menjadi 86,2%. Hal ini dikarenakan edukasi yang interaktif efektif dalam meningkatkan pemahaman siswa mengenai bahaya penyalahgunaan Napza dan pentingnya kesehatan reproduksi bagi remaja. Kesimpulan, dengan adanya kegiatan penyuluhan ini para siswa-siswi mampu meningkatkan pemahaman mereka tentang bahaya penyalahgunaan Napza dan pentingnya kesehatan reproduksi bagi remaja.